Cytolethal Distending Toxin Subunit B: A Review of Structure–Function Relationship - Pons, Benoît J. (Toxins (Basel), 2019)
The Cytolethal Distending Toxin (CDT) is a bacterial virulence factor produced by several Gram-negative pathogenic bacteria. These bacteria, found in distinct niches, cause diverse infectious diseases and produce CDTs differing in sequence and structure. CDTs have been involved in the pathogenicity of the associated bacteria by promoting persistent infection. At the host-cell level, CDTs cause cell distension, cell cycle block and DNA damage, eventually leading to cell death. All these effects are attributable to the catalytic CdtB subunit, but its exact mode of action is only beginning to be unraveled. Sequence and 3D structure analyses revealed similarities with better characterized proteins, such as nucleases or phosphatases, and it has been hypothesized that CdtB exerts a biochemical activity close to those enzymes. Here, we review the relationships that have been established between CdtB structure and function, particularly by mutation experiments on predicted key residues in different experimental systems. We discuss the relevance of these approaches and underline the importance of further study in the molecular mechanisms of CDT toxicity, particularly in the context of different pathological conditions.